Percepción de calidad del servicio de la empresa de transportes Royal Travel S.C.R.L., Trujillo- Quiruvilca; mediante modelo servqual -2016 - Cueva Paredes, Noemí (2016)
This research was conducted to know the perception of quality of service provided by the transport company "ROYAL TRAVEL S. C. R. L." in the path of Trujillo Quiruvilca. For which a simple random sample of 223 users of a finite population 01 manager and 21 workers was used. interview technique addressed to the manager, a questionnaire survey of staff and survey SERVQUAL model adapted to passenger transport was applied; measuring 22 indicators related to quality dimensions as: Tangibles, Reliability, Responsiveness, Security, Empathy and intervening variables (demographic and Preferences) in the Likert scale with 5 levels to know the degree of agreement or disagreement users according to the perceived service. The socio-demographic profile obtained for both users and staff; also the view of manager .The user profile is characterized by traveling weekly and monthly in the evening and morning hours, preferring to travel in the company by the proximity of the terminal and security, as well as the nearest competitor the company has Entravesa ; There is also lack of training, lack of incentives and motivation to staff. Coming to determine that the company is providing quality average service, not so efficient, since it has a high quality level in the reliability dimension, while the dimensions Responsiveness, Security and empathy have average quality, without But the tangibility dimension has a low level of quality as perceived by the user of the company. Finally recommendations based on the SERVQUAL, Zener model and theory of expectations to improve the quality of service is given